2021
DOI: 10.3389/fcimb.2021.744163
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Leishmania braziliensis DNA in the Nasal Mucosa of Cutaneous Leishmaniasis Patients and the Search for Possible Clinical and Immunological Patterns of Disease Progression: A Cross Sectional Study

Abstract: Leishmania braziliensis is the most important causal agent of American tegumentary leishmaniasis (ATL), and 3 to 5% of patients develop mucosal lesions. The mechanisms related to parasite and host immune interactions and the parasite life cycle that lead to dissemination to the mucosa are poorly understood. We aimed to detect L. braziliensis DNA in the nasal mucosa of cutaneous leishmaniasis (CL) patients with early mucous dissemination and to relate those findings to specific inflammatory responses. Nasal swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The findings of this study provide a warning for the possible association between L. (V.) shawi and mucous lesions, since L. (V.) braziliensis can be found both in normal mucosa and in injured mucosa [5]. Experimental studies showed that infection by L. (V.) shawi without symptoms in mice can occur through the activation of antigens capable of inducing a protective immune profile, which is important for the development of vaccines against TL [34,35].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The findings of this study provide a warning for the possible association between L. (V.) shawi and mucous lesions, since L. (V.) braziliensis can be found both in normal mucosa and in injured mucosa [5]. Experimental studies showed that infection by L. (V.) shawi without symptoms in mice can occur through the activation of antigens capable of inducing a protective immune profile, which is important for the development of vaccines against TL [34,35].…”
Section: Discussionmentioning
confidence: 76%
“…L. (V.) braziliensis causes more frequently disseminated conditions, being the main species causing mucosal leishmaniasis [4]. L. (V.) braziliensis can be detected in the nasal mucosa of both sick and healthy people living in areas with endemic TL [5]. L. (V.) guyanensis, which is predominant in certain endemic areas of northern Brazil, notably in the states of Amazonas and Amapá [6], can also cause mucosal lesions [7] and is highly resistant to Glucantime, the first-line drug treatment for TL in Brazil [2].…”
Section: Introductionmentioning
confidence: 99%
“…After a study of 26 well-registered cases, authors reached to the conclusion that pregnancy has influence on clinical manifestations when the causative parasite is L. (V.) braziliensis, because all studied women presented painless large lesions with an atypical exophytic appearance [28]. Machado et al [29] and Barroso et al [30] describe that disseminated leishmaniasis caused by L. (V.) braziliensis is associated with immunosuppression and specific inflammatory responses, in which there is a decrease in IL-12 cytokines in the peripheral blood and attraction of Th1 cells activated by the protozoan in the multiple skin lesions. However, they did not present any important inflammation signs, such as the pictures we present of our present patient in Ecuador, whose lesions were not atypical neither vegetative nor exophytic but larger than usual, strongly inflammatory, and painful, although there was no secondary infection.…”
Section: Discussionmentioning
confidence: 99%